Effect of General Anesthesia on Auditory Brainstem Response Testing - Ogulcan GUNDOGDU; Handan YAMAN; Pelin KARAASLAN; Mustafa Bulent SERBETCIOGLU (Medeniyet Medical Journal)
Objective: The auditory brainstem response (ABR) test is usually applied during natural sleep, but it can also be conducted under anesthesia. This retrospective study aimed to compare the ABR findings of a general anesthesia group and a control group that underwent ABR test during natural sleep. Methods: The anesthesia group consisted of 42 (mean age 44.5+-20.3 months) children, and the control group included 58 children (36.1+-16.1 months). The results of the click ABR test of the two groups were compared in terms of amplitude, latency, interpeak latencies, and hearing thresholds. Results: The amplitudes of waves III and V were significantly decreased in the general anesthesia group compared with that in the control group. The ABR latencies of waves I and V and the interpeak latencies for I-V and III-V were prolonged in the anesthesia group compared with that in the control group. Moreover, the click threshold obtained in the anesthesia group was significantly higher than those of the control group. Conclusions: Clinicians and audiologists should advise families to know the effects of general anesthesia on ABR and be cautious in interpreting the results obtained in ABR test performed under anesthesia.